'A lot of catching up', knowledge gaps and emotions in the development of a tactical collective identity among students participating in solidarity with the Winnemem Wintu. (2nd October 2017) - Bacon, J. M.
ABSTRACT: Settler-colonialism generates significant knowledge gaps and emotional barriers to cross-cultural mobilization, but does not prohibit meaningful solidarity. Through participant observation and semi-structured interviews with non-indigenous university students in solidarity with the Winnemem Wintu between 2011 and 2013, I observe that during acts of solidarity students recognize colonization as an ongoing phenomenon in which they are implicated. This knowledge acquisition often elicits shame and guilt, feelings that students must manage in order to be effective allies while simultaneously navigating the pervasive concept that guilt has no place in solidarity work. Drawing from sociology of emotions, social movement theories, and social-psychological analyses of collective guilt and shame, I explore how emotions influence methods of settler-solidarity.